2021
DOI: 10.1161/circresaha.120.316711
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial S1P 1 Signaling Counteracts Infarct Expansion in Ischemic Stroke

Abstract: Rationale: Cerebrovascular function is critical for brain health, and endogenous vascular-protective pathways may provide therapeutic targets for neurological disorders. Sphingosine 1-phosphate (S1P) signaling coordinates vascular functions in other organs, and S1P receptor-1 (S1P 1 ) modulators including fingolimod show promise for the treatment of ischemic and hemorrhagic stroke. However, S1P 1 also coordinates lymphocyte trafficking, and lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 81 publications
11
96
1
Order By: Relevance
“…S1PR1 is mainly expressed in microvascular endothelial cells and plays a critical role in promoting barrier integrity (64,65), sproutings (62), angiogenesis maturation (66)(67)(68), and nitric oxide generation (69). Endothelium-specific S1PR1knockout mice exhibit impaired blood-brain-barrier integrity and increased adhesion molecule expressions in a middle cerebral artery occlusion-induced stroke model (70)(71)(72). Cardiomyocyte-restricted deletion of S1PR1 shows progressive cardiomyopathy and premature death due to impaired activity of sarcolemmal Na + /H + exchange and increased Ca 2+ sensitivity (73).…”
Section: Discussionmentioning
confidence: 99%
“…S1PR1 is mainly expressed in microvascular endothelial cells and plays a critical role in promoting barrier integrity (64,65), sproutings (62), angiogenesis maturation (66)(67)(68), and nitric oxide generation (69). Endothelium-specific S1PR1knockout mice exhibit impaired blood-brain-barrier integrity and increased adhesion molecule expressions in a middle cerebral artery occlusion-induced stroke model (70)(71)(72). Cardiomyocyte-restricted deletion of S1PR1 shows progressive cardiomyopathy and premature death due to impaired activity of sarcolemmal Na + /H + exchange and increased Ca 2+ sensitivity (73).…”
Section: Discussionmentioning
confidence: 99%
“…In the central nervous system, S1P receptor agonists improve neurovascular microcirculation, strengthen brain endothelial barrier function thereby limiting plasma and leukocyte extravasation, and support cell survival. 15,16 More specifically, activation of S1PR1 reduces plaque density and amyloid levels in models of Alzheimer's disease and slows down disease progression in mouse models of Huntington's disease. 8,9 From a translational perspective, it is worth mentioning that a clinical pilot trial using fingolimod revealed some beneficial effects of the drug in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets store large amounts of S1P that is only released upon activation (Nitzsche et al, 2021). CD62P, also known as P-selectin, can directly reflect the activation of platelets in vivo and interact with leukocytes to potentiate vascular injury.…”
Section: Dscxq Reduced Immunoreactive Cells Of Cd62pmentioning
confidence: 99%
“…A large number of documents show that Sph kinase (SphK), which phosphorylates Sph to form S1P, is a key regulator of the sphingolipid rheostat (Spiegel and Milstien, 2003), and SphK1 has been proved as the dominant kinase for S1P production in the brain and exert a critical role in "sphingolipid rheostat" (Maceyka et al, 2002;Blondeau et al, 2007). S1P receptors, S1PR1 is amongst the most abundant subtype of S1P receptors in the brain, which plays a crucial role in sustaining hallmark endothelial functions and could be as a regulator for microglial activation following cerebral ischemia (Moon et al, 2015;Nitzsche et al, 2021). S1P can activate platelets, which in turn stimulates the release of S1P into the bloodstream, S1P bind to receptors on the platelet surface, altering cell membrane glycoproteins, exposing fibrinogen receptors, increasing CD62P expression and activation rates and elevating platelet reactivity (Huang et al, 2006).…”
Section: Sphingomyelin Metabolism and Apoptosis In Strokementioning
confidence: 99%